2014
DOI: 10.1007/s11033-014-3037-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and validation of potential pathogenic microRNAs involved in Phytophthora infestans infection

Abstract: Being one kind of approximately 22nt long small RNA, miRNA has shown its roles in host-pathogen interaction, providing one possible way for pathogen infection. Though Phytophthora infestans is a major pathogen that causes devastating late blight of potato, tomato and so on, so far there have not been any systematic researches on miRNAs and even pathogenic miRNAs in P. infestans. Here, for the first time we comprehensively predicted and identified pathogenic miRNAs that may exist in P. infestans. First, a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…After 10 days, the cellophane, which was filled with P. infestans, was transferred to a new culture dish. Tomato leaves were used to cover the upper and lower sides of this cellophane as described previously31. P. infestans s amples were collected from the cellophane at 0, 3, 12, 24, 36, 48 and 72 hpi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 days, the cellophane, which was filled with P. infestans, was transferred to a new culture dish. Tomato leaves were used to cover the upper and lower sides of this cellophane as described previously31. P. infestans s amples were collected from the cellophane at 0, 3, 12, 24, 36, 48 and 72 hpi.…”
Section: Methodsmentioning
confidence: 99%
“…MiR1918 is expressed in all tomato tissues, and it was initially thought to be involved in the regulation of fruit development and maturation30. Recently, a number of P. infestans miRNAs (pi-miRNAs) have been predicted using P. infestans EST data and all the known miRNAs from miRBase, and pi-miR1918 is among these predicted pi-miRNAs, and its level was found to change dramatically in P. infestans -infected Solanum pimpinellifolium leaves31. In addition, a recent silico study has shown that tomato miR1918 might bind to the AC1 gene coding the replication-related protein in Tomato leaf curl virus (ToLCV).…”
mentioning
confidence: 99%
“…The pathogen P. infestans was cultured according to Cui et al (2014). P. nicotianae was cultured at 28°C for 2 weeks in carrot medium.…”
Section: Pathogen Response Assaysmentioning
confidence: 99%
“…P. infestans was cultured in oat medium according to the method described by Cui, Luan, Wang, and Zhai (). B. cinerea was cultured on potato dextrose agar medium supplemented with 20 g L −1 sucrose in the dark at 20°C for 12 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Polymerase chain reaction was used to amplify the cDNA fragments of the 2.7 | Pathogens culture and pathogenicity assays P. infestans was cultured in oat medium according to the method described by Cui, Luan, Wang, and Zhai (2014). B. cinerea was cultured on potato dextrose agar medium supplemented with 20 g L −1 sucrose in the dark at 20°C for 12 hr.…”
Section: Virus-induced Gene Silencing (Vigs)mentioning
confidence: 99%